Treatment of drug‐induced seizures. (17th September 2015) - Chen, Hsien‐Yi; Albertson, Timothy E.; Olson, Kent R.
Abstract : Seizures are a common complication of drug intoxication, and up to 9% of status epilepticus cases are caused by a drug or poison. While the specific drugs associated with drug‐induced seizures may vary by geography and change over time, common reported causes include antidepressants, stimulants and antihistamines. Seizures occur generally as a result of inadequate inhibitory influences (e.g., gamma aminobutyric acid, GABA) or excessive excitatory stimulation (e.g. glutamate) although many other neurotransmitters play a role. Most drug‐induced seizures are self‐limited. However, status epilepticus occurs in up to 10% of cases. Prolonged or recurrent seizures can lead to serious complications and require vigorous supportive care and anticonvulsant drugs. Benzodiazepines are generally accepted as the first line anticonvulsant therapy for drug‐induced seizures. If benzodiazepines fail to halt seizures promptly, second line drugs include barbiturates and propofol. If isoniazid poisoning is a possibility, pyridoxine is given. Continuous infusion of one or more anticonvulsants may be required in refractory status epilepticus. There is no role for phenytoin in the treatment of drug‐induced seizures. The potential role of ketamine and levetiracetam is promising but not established.